Intermediate Algebra (6th Edition)

Published by Pearson
ISBN 10: 0321785045
ISBN 13: 978-0-32178-504-6

Chapter 9 - Review: 2



Work Step by Step

We are given that $f(x)=x-5$ and $g(x)=2x+1$. We know that $(f-g)(x)=f(x)-g(x)$. Therefore, $(f-g)(x)=f(x)-g(x)=(x-5)-(2x+1)=x-2x-5-1=-x-6$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.